Role of oxygen content on micro-whiskers in mercury based superconductors - (:unkn) unknown (ELSEVIER, 2015)
In this study, the formation of micro-whiskers at the mercury based cuprate superconductors, synthesized by solid state reaction technique has been investigated for both oxygen and argon annealed samples. In this context, the superconducting samples have been annealed by the oxygen or argon gases in same rate (pressure) of 150 bar. Moreover, the over doped sample has been subjected to oxygen annealing twice at the same oxygen rate. Hence, micro-whiskers in the mercury cuprates have spontaneously grown for the over oxygen annealed sample, so we have not intended to have whisker grown. The whiskers grown in the mercury based cuprate superconductor has been investigated by Scanning Electron Microscopy, X-Ray Diffraction analysis and Superconducting Quantum Interference Devices measurements for the first time It has been determined that whiskers grown on the over doped sample, which are in micrometer dimensions, have been observed only surfaces of the bulk sample. Moreover, the formation of whiskers has been examined for the optimally oxygen and argon doped samples It has been shown that neither the optimally oxygen doped nor argon (loped samples with the same gas rate have displayed any whisker structures. Hence, it has been decided that that the type of gas, the density of gas flowing and the bulk properties of the superconductor play a crucial role on formation of whisker structure in the system. Moreover, it has been revealed that in order to get rich whisker content, the oxygen process should be applied to the powder form of the superconductor in such a way to get the over oxygen doping rate for the superconducting system investigated. For further works, the magnetic and transport properties of the mercury based whiskers grown are planned to be determined. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Mercury cuprate superconductor; The formation of micro-whisker; Role of gas type and concentration on formation of whisker; SINGLE-CRYSTAL WHISKERS; BI2SR2CACU2O8+DELTA WHISKERS; GROWTH; FABRICATION